1997
DOI: 10.1097/00004728-199707000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Scaphoid Fractures in Skeletally Immature Patients: Application of MRI

Abstract: A normal initial MR image had a negative predictive value of 100%. Persistent snuffbox pain may represent injury to the scaphoid, extensor tendons, or dorsal soft tissues. An outcome study evaluating the benefits of early application of MR in the pediatric population is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Many recent studies suggest equal sensitivity and better (sometimes 100%) specificity for MR imaging in accurately detecting radiographically occult scaphoid fractures [3,4,15,16]. On MR imaging, the fracture line will appear as a discrete focus of linear low T1 and T2 signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies suggest equal sensitivity and better (sometimes 100%) specificity for MR imaging in accurately detecting radiographically occult scaphoid fractures [3,4,15,16]. On MR imaging, the fracture line will appear as a discrete focus of linear low T1 and T2 signals.…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al [16] studied 18 skeletally immature patients who had presented to the emergency department within 2 days of acute wrist trauma. Those authors reported normal findings on initial MR images to have a negative predictive value of 100%.…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…2). Scaphoid fractures not visible on initial plain radiographs are reported to occur from 7% to 80% [12][13][14][15]. A large meta-analysis showed that occult fractures correspond to approximately 16% of all scaphoid fractures [16].…”
Section: Fractures and Microfracturesmentioning
confidence: 99%
“…A large meta-analysis showed that occult fractures correspond to approximately 16% of all scaphoid fractures [16]. MRI is able to disclose occult fractures offering 100% sensitivity, 100% specificity [16][17][18][19] and in the immature skeleton a negative predictive value of 100% [14]. The fracture is shown as a low signal intensity line on all MR sequences extending from cortex to cortex (Fig.…”
Section: Fractures and Microfracturesmentioning
confidence: 99%